WEGENER GRANÜLOMATOZİS: FULMİNAN SEYREDEN BİR OLGU - Eyibilen, Ahmet (Fırat University, 2002)
Wegener granülomatozis (WG) birden fazla sistemi tutabilen, vaskülit, granülomatozis ve nekrozla kendini gösteren enflamatuar bir hastalıktır. Klasik formu üst ve alt solunum yolu ile böbrekleri tutmasına karşın, gerçekte herhangi bir organı tutabilir. Hastaların yaklaşık %80-90'ında burun ve paranazal sinüsler tutulur. Bu yazıda iki ay kronik sinüzit tanısıyla tedavi edilmeye çalışılan Wegener granülomatozisli bir kadın hasta sunuldu. Hastaya siklofosfamid ve prednizondan oluşan bir tedavi uygulanmasına rağmen hasta kaybedildi. Bu olgu erken tanıda kulak burun boğaz muayenesinin (KBB) önemini vurgulamak amacıyla sunulmuştur.

Wegener's granulomatosis is a multisystem inflammatory disease characterized by vasculitis, granuloma formation and necrosis. Although the classic form of Wegener's granulomatosis involves the upper and lower respiratory tract and the kidney, virtually any organ system can be affected. Involvement of the nasal and paranasal sinuses occurs in %80-90 of patients. This paper presents a woman patient with Wegener's granulomatosis tried to be threated two months by diagnosis of chronic sinusitis. Although the patient is given with a protocol consisting of cyclophosphamide and prednisone, the patient died. This case is presented to bring out the important of otolaryngologic examination in early diagnosis.
Wegener's Granulomatosis: Fulminant Progressed A Case Report